Soil-Forming and Evolution Related to the Geological Formations, A Case Study of the Southern Part of Urmia Plain - Javadi, Hengameh; Masihabadi, Mohammad Hassan; Sokouti, Reza; Pazira, Ebrahim (Revista de la Universidad del Zulia, 2020)
The objective of this article was to study the effect of geographical features and geological formations on some physicochemical properties of soils in order to better identify the soil and optimize land management for sustainable agriculture in the southern part of the plain. Urmia, with an area of 35000 (ha) in the province of Western Azarbaijan, Iran. In this investigation, satellite images, aerial photographs, topographic and geological maps were used to identify and distinguish different land forms, soil series classified based on geomorphological and geophysical methods. 30 soil profiles were drilled and the FAO standard dimensions were described. Samples were taken from five soil profiles in each genetic horizon and transferred to the laboratory. The soil moisture and temperature regime was determined as Xeric and Mesic. The soils of the studied area were classified as Fluventic Inceptisols and grid subgroups. The most dominant formations in the Barandoz and Ghasemlou river basins were limestone and lime, which is one of the determining factors in rock formation in different soils in the study area. On the other hand, physiography and topography have also played an important role, so that the upper terraces have more developed soils and some sloping regions have younger and less developed soils. With the decrease in height and proximity to Lake Urmia, the effect of the groundwater level and its salinity on the profiles is evident. Meanwhile, the river bank has young and uncovered soils due to the sediments of the current era.